Aging, rhythms of physical performance, and adjustment to changes in the sleep-activity cycle. Issue 11 (November 1997) - Reilly, T; Waterhouse, J; Atkinson, G
Abstract : OBJECTIVES: Shiftwork causes disturbances of the normal sleep-wake cycle and circadian rhythm. There is concern that aging workers have more problems than younger counterparts when the human body clock is disrupted. This review considers issues relating to aging, the circadian body clock, and adjustment to altered sleep-wake schedules. METHODS: Reports on effects of aging on the human body clock were reviewed. Research concerned with adjustment to circadian phase shifts (as occurs in night work) was considered. RESULTS: With aging there is an increased tendency towards morningness which is linked with difficulties in sleeping. The peak time and amplitude of normal circadian rhythms are altered. Tolerance of shiftwork can be linked with social factors as well as adaptation of the body clock. CONCLUSIONS: People habituated to night work seem to have developed mechanisms which allow them to cope with disruptions to lifestyle and the endogenous body clock. Elderly people are more suited to phase advances, as occur in morning workshifts, than to phase delays such as nocturnal work.